Global Cephalometric Norms for Pediatric Soft Tissue Profiles: A Systematic Review and Meta-Analysis of Racial and Ethnic Variations - Asep Darya Darma Putra; Yona ladyventini; Bobby (Open Access Indonesian Journal of Medical Reviews, 2025)
The diagnostic standards in orthodontics have been historically based on Caucasian cephalometric norms, an approach that is increasingly inappropriate for a diverse global population and can lead to misdiagnosis in pediatric patients aged 9-18. This study aimed to systematically review the literature and perform a meta-analysis to establish and compare key soft tissue cephalometric estimates for pediatric populations across various major racial and ethnic groups. Following PRISMA guidelines, a comprehensive search of PubMed, Scopus, Web of Science, and Embase was conducted for studies published between January 2015 and August 2025. We included cross-sectional studies reporting mean and standard deviation for soft tissue cephalometric measurements in untreated adolescents from distinct ethnic groups. Two reviewers independently performed study selection, data extraction, and risk of bias assessment using the Newcastle-Ottawa Scale. A random-effects model was used to calculate pooled mean estimates, 95% confidence intervals (CI), and 95% prediction intervals (PI) for key parameters. The search yielded 1,842 articles; seven studies met the inclusion criteria, comprising 1,240 individuals. Significant differences in pooled means were found across all parameters, with profound statistical heterogeneity. Subjects of African descent displayed the most convex facial profile (pooled mean G’-Sn-Pog’: 164.8°; 95% CI: 163.1-166.5; I²=92%). In contrast, Caucasian subjects exhibited the straightest profile (172.5°; 95% CI: 170.9-174.1). Lip prominence was greatest in the African descent group (+3.5 mm to E-line; 95% CI: 2.8-4.2; I²=91%) and retrusive in the Caucasian group (-2.1 mm; 95% CI: -2.8 to -1.4). The 95% prediction intervals were substantially wider than the confidence intervals, highlighting extensive inter-population variance. In conclusion, clinically significant variations in pediatric soft tissue profiles exist among different racial and ethnic groups. The extreme heterogeneity found in this analysis is a critical finding, suggesting that the concept of a single numerical "norm" is flawed even within broad ethnic categories. This meta-analysis provides a quantitative foundation for a more cautious, individualized diagnostic approach that respects the wide spectrum of normal human facial variation.